The transition to teletherapy in marriage and family therapy training settings during COVID‐19: What do the data tell us?. (20th March 2021) - Morgan, Amy A.; Landers, Ashley L.; Simpson, Jessica E.; Russon, Jody M.; Case Pease, Jenene; Dolbin‐MacNab, Megan L.; Bland, Krista N.; Jackson, Jeffrey B.
Abstract: In the wake of the COVID‐19 pandemic, little is known about how university training programs transitioned to teletherapy. This study describes the transition of two university marriage and family therapy (i.e., master's and doctoral) training clinics to teletherapy and presents preliminary analyses of the types of clients and cases that converted to teletherapy. A series of chi‐square analyses, a t‐test, a logistic regression model, and a multiple linear regression model were employed. Four key findings emerged: (1) most cases converted to teletherapy; (2) Hispanic ethnicity was the only demographic characteristic to significantly predict conversion to teletherapy; (3) individual cases were significantly more likely to convert to teletherapy than relational cases; and (4) the number of prior in‐person sessions attended significantly predicted conversion to teletherapy. Teletherapy conversion implications are discussed across four systemic levels: client, student trainee, supervision, and larger systems.